1981
DOI: 10.1073/pnas.78.12.7665
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced graphic matrix analysis of nucleic acid and protein sequences.

Abstract: GeneticsEnhanced graphic matrix analysis of nucleic acid and protein sequences (sequence homology/transposition/secondary structure/immunoglobulin/microcomputer) JACOB V. MAIZEL, JR., AND ABSTRACT The enhanced graphic matrix procedure analyzes nucleic acid and amino acid sequences for features ofpossible biological interest and reveals the spatial patterns ofsuch features. When a sequence is compared to itselfthe technique shows regions of self-complementarity, direct repeats, and palindromic subsequences. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(172 citation statements)
references
References 29 publications
0
172
0
Order By: Relevance
“…In this study, we have performed a systematic analysis of PHAX, and revealed three important interaction domains within the protein that are all required for U snRNA export+ First, we have mapped NLSs of PHAX that are required for recycling of PHAX to the nucleus+ Second, we have found that the evolutionarily conserved region of PHAX is a novel RNA-binding domain required for mediating U snRNA export+ Third, the interaction domain of PHAX with CBC was shown to be at least partly distinct from the NLSs and the RNA-binding domain+ Our previous work had shown that the NEScontaining region of PHAX, together with PHAX phosphorylation, is required for interaction between PHAX and CRM1/Exportin1 (Ohno et al+, 2000)+ Thus, mutant forms of PHAX that allow the effects of its various in- (Maizel & Lenk, 1981) from the Wisconsin Package, version 10+1, Genetics Computer Group (GCG), with the settings of stringency 13 and window 35+ B: Sequence alignment of mouse PHAX (amino-acid residues 215-327) with the corresponding regions from rat (X67877), human (AW607076), newt (CAB54141), X. laevis (AW147615, AW148211), Drosophila melanogaster (AAF58985), C. elegans (AAF36030) and Arabidopsis thaliana (BAB02826)+ Sequences were compiled and analyzed using BLAST (Altschul et al+, 1997) and Clustal_X (Thompson et al+, 1998), and displayed using the BOXSHADE 3+21 program (http://www+ch+embnet+org/software/BOX_form+html)+ The residues indicated by closed circles in the mouse sequence were replaced by alanines in the CM1-7 mutants+ C: Poly U Sepharose binding assay with the alanine mutants+ The experiment was performed as in Figure 4+ D: Quantitation of RNA-binding activity of the alanine mutants from three experiments similar to C+ teractions on function in U snRNA export to be tested have now been generated and analyzed+…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have performed a systematic analysis of PHAX, and revealed three important interaction domains within the protein that are all required for U snRNA export+ First, we have mapped NLSs of PHAX that are required for recycling of PHAX to the nucleus+ Second, we have found that the evolutionarily conserved region of PHAX is a novel RNA-binding domain required for mediating U snRNA export+ Third, the interaction domain of PHAX with CBC was shown to be at least partly distinct from the NLSs and the RNA-binding domain+ Our previous work had shown that the NEScontaining region of PHAX, together with PHAX phosphorylation, is required for interaction between PHAX and CRM1/Exportin1 (Ohno et al+, 2000)+ Thus, mutant forms of PHAX that allow the effects of its various in- (Maizel & Lenk, 1981) from the Wisconsin Package, version 10+1, Genetics Computer Group (GCG), with the settings of stringency 13 and window 35+ B: Sequence alignment of mouse PHAX (amino-acid residues 215-327) with the corresponding regions from rat (X67877), human (AW607076), newt (CAB54141), X. laevis (AW147615, AW148211), Drosophila melanogaster (AAF58985), C. elegans (AAF36030) and Arabidopsis thaliana (BAB02826)+ Sequences were compiled and analyzed using BLAST (Altschul et al+, 1997) and Clustal_X (Thompson et al+, 1998), and displayed using the BOXSHADE 3+21 program (http://www+ch+embnet+org/software/BOX_form+html)+ The residues indicated by closed circles in the mouse sequence were replaced by alanines in the CM1-7 mutants+ C: Poly U Sepharose binding assay with the alanine mutants+ The experiment was performed as in Figure 4+ D: Quantitation of RNA-binding activity of the alanine mutants from three experiments similar to C+ teractions on function in U snRNA export to be tested have now been generated and analyzed+…”
Section: Discussionmentioning
confidence: 99%
“…Once sequences were obtained, manipulations were performed using ESEE (Cabot and Beckenbach 1989). Dot-plot comparisons were performed using the algorithm of Maizel andLenk (1981) available in GCG (Genetics Computer Group, Madison, WI, Version 8.0, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Another alternative to nonhomologous recombination is that the PSR2 repeat family evolved from NATE. To determine if there were large-scale similarities between the PSR2 sequence and the region of NATE underlying the junction, dot-plot comparisons (Maizel and Lenk 1981) were performed. A 229-bp region of NATE P5 leading up to the junction site, the four PSR2 repeats, and 100 bp of NATE P16 on the other side of the junction site were joined into a composite sequence and this was compared to the PSR2-1 sequence.…”
Section: Origin Of the Nate/psr2 Junctionmentioning
confidence: 99%
“…Proline residues are thought to be important in protein-protein interactions [40] and this region may be important in interacting with the H or I subunits. Figure 3 shows a Dot-plot comparison [41] of the subunit I consensus sequence shown in Figure 1 with a subunit D consensus generated from the three D subunit sequences. Diagonal lines on this Figure show regions of similarity between the two compared sequences, and it is obvious that the N-terminal of the D subunits show similarity to the I subunit.…”
Section: Figure 2 Consensus Of I Subunits Showing the Three Conservedmentioning
confidence: 99%